HYDROLOGICAL ANALYSIS AND DESIGN OF SURFACE DRAINAGE FACILITIES FOR AIRFIELDS IN ARCTIC AND SUBARCTIC REGIONS. - Johnson,Loyal A. (1951)
The report is a suggested modification of Part 13, Chapter 1, 'Surface Drainage Facilities for Airfields,' of the Engineering Manual for War Department Construction. The modifications are intended to make possible the application of methods contained in the initial report to arctic and subarctic conditions. The original outline has been followed quite closely. Essential differences are (1) a new design storm index to fit Alaskan conditions, (2) new supply curves to match rainfall intensities, frequencies, and durations in Alaska, (3) elimination of ponding, (4) addition of a list showing recommended practices, and (5) addition of a few paragraphs on the subject of icings. Also included are maps, diagrams, and drawings. (Author)